The role of teachers in creating interest in education in primary school students in Parsian - Mashinchi, Ali Asghar; Akbari, Alireza (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to investigate the role of teachers in creating interest in education in primary school students in Parsian. This is an applied survey one. The statistical population of this research includes 50 elementary school teachers in Parsian. Since the size of the community was small and the elements are available, sampling has not been done and all the teachers have been studied. The data gathering tool in this research is a researcher-made questionnaire based on the research needs with 45 closed questions. The validity of the questionnaire was based on the experts’ perspective and their reliability was based on the Cronbach’s alpha coefficient. The reliability of the questionnaire was 0.813 which indicates the desirable reliability of the research questionnaire. Descriptive statistics (frequency, percentage, standard deviation and variance) and inferential statistics (one sample t test and Friedman test) were used to analyze the data. The results of this research indicate that teachers have a significant and meaningful role in motivating and interesting in studying elementary school students